STUDY ON SYNTHESIS AND CYTOTOXIC ACTIVITY OF GONIOTRIOL, DIMER- GONIOTRIOL, HOWIINOL A AND THEIR PRECURSOR - Hùng, Nguyễn Văn; Hạnh, Nguyễn Thị Hồng; Hương, Đoàn Thị Mai; Cường, Phạm Văn; Châm, Bá Thị (Vietnam Journal of Science and Technology, 2012)
SUMMARY The styryl-lactones belong to a group of secondary metabolites commonly isolated from the family Annonaceae. Among them, Howiinol A (12) has shown in vitro cytotoxic effect against the cancer cell line L1210 and goniotriol (13) has shown in vitro cytotoxic effect against the cancer cell line MCF7. Recently, we have announced the synthesis of howiinol A. Herein, we report the synthesis of goniotriol (13) and dimer-goniotriol (14) from precursor 10. Simultaneously, cytotoxic evaluation of these compounds againts several cancer cell lines was performed. One of them, specially, compound 11 has high activity against 4 human cancer cell lines LU-1, HepG2, KB và MCF7 with IC50 = 0.53, 0.71, 0.66 and 0.58 μg/ml, respectively.